Rubber composition and battery
The rubber composition, with a specific formulation of metal hydroxides and a matrix polymer of liquid rubber and solid elastomer, addresses the issues of flexibility and adhesiveness in existing fire-resistant resin compositions, achieving rapid fire extinguishment and effective tracking on battery cells.
Patent Information
- Application Number
- JP2024019006
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2024-02-09
- Publication Date
- 2025-04-17
- Estimated Expiration
- 2044-02-09
AI Technical Summary
Existing fire-resistant resin compositions used in battery applications suffer from impaired flexibility and adhesiveness due to the high content of inorganic compounds, leading to potential gaps in coverage and increased risk of external fires.
A rubber composition is developed, comprising 50 to 2000 parts by mass of metal hydroxides per 100 parts by mass of matrix polymer, with the matrix polymer consisting of a liquid rubber and a solid elastomer in a mass ratio of 95:5 to 50:50, and is formulated as a putty-like composition for effective adhesion and tracking.
The rubber composition achieves rapid fire extinguishment, excellent adhesiveness, workability, and tracking properties, allowing it to effectively follow the shape of cylindrical battery cells and prevent external fires.
Smart Images

Figure 0007664441000004 
Figure 0007664441000005 
Figure 0007664441000001
Abstract
Description
[Technical field]
[0001] The present invention relates to a rubber composition and a battery. In particular, the rubber composition is a putty-like composition and is mainly used for batteries. [Background technology]
[0002] In various batteries such as lithium batteries, an internal short circuit or the like can cause a battery cell to go into thermal runaway, resulting in fire, smoke, etc. In order to prevent problems caused by such thermal runaway, there have been attempts to use protective materials such as fireproof materials and insulating layers around the battery cells. It is expected that such protective materials will make it difficult for the heat of a high-temperature battery cell to propagate to other battery cells and to the housing that houses the battery cells.
[0003] For example, Patent Document 1 discloses a fire-resistant resin composition containing a heat-absorbing agent having a thermal decomposition starting temperature of 800° C. or lower and an endothermic amount of 300 J / g or more, and a resin. [Prior art documents] [Patent documents]
[0004] [Patent Document 1] Patent Publication 2019-143139 Summary of the Invention [Problem to be solved by the invention]
[0005] The fire-resistant resin composition of Patent Document 1 is, for example, a fire-resistant resin composition that is made by blending a large amount of aluminum hydroxide into EVA resin, and is capable of quickly extinguishing a fire caused by a battery in a mobile phone, etc. However, blending a large amount of inorganic compounds into the resin impairs flexibility and adhesion, and the resin is unable to conform to the cylindrical battery cell, leaving gaps that may allow a fire to break out to the outside.
[0006] Therefore, the present invention provides a rubber composition that can extinguish a fire caused by a sudden temperature rise in a battery cell in a short period of time, and has excellent adhesion, workability, and conformability to the object to be protected. [Means for solving the problem]
[0007] The present inventors have conducted extensive research to solve the above problems, and as a result have found that the above problems can be solved by using a composition with a specific blend ratio, which has led to the completion of the present invention.
[0008] That is, according to the present invention, the following inventions are provided. [1] 50 to 2000 parts by mass of a metal hydroxide per 100 parts by mass of a matrix polymer; The rubber composition, wherein the matrix polymer contains a liquid rubber and a solid elastomer, and the mass ratio of the liquid rubber to the solid elastomer is 95:5 to 50:50. [2] The rubber composition according to [1], wherein the metal hydroxide includes aluminum hydroxide. [3] The rubber composition according to [1] or [2], which is in a putty form. [4] The rubber composition according to any one of [1] to [3], which is used for a battery. [5] A battery comprising a member made of the rubber composition according to any one of [1] to [4]. Effect of the Invention
[0009] According to the present invention, it is possible to provide a rubber composition that can extinguish a fire caused by a sudden temperature rise of a battery in a short time and has excellent adhesion, workability, and conformability to a protected object. Such a rubber composition has an appropriate softness and can be used as a putty-like protective material that can conform to the shape of a cylindrical battery cell. [Brief description of the drawings]
[0010] [Figure 1]Fig. 1A is a schematic diagram showing a state in which a rubber composition is attached to a surface of a cylindrical battery cell, and Fig. 1B is a schematic diagram showing a state in which the rubber composition is attached to the surface of a cylindrical battery cell. [Diagram 2] FIG. 2 is a schematic diagram showing the adhesion test. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0011] Hereinafter, an embodiment for carrying out the present invention (hereinafter referred to as "the present embodiment") will be described in detail, but the present invention is not limited thereto, and various modifications are possible within the scope of the present invention. Such a rubber composition is a composition with excellent deformability, and can be used as a putty that can be easily used according to the shape. In other words, the composition can also be provided as a putty-like fire-resistant composition.
[0012] The rubber composition of the present embodiment includes a matrix polymer and a metal hydroxide. The matrix polymer includes a liquid rubber and a solid elastomer, and the mass ratio of the liquid rubber to the solid elastomer is 95:5 to 50:50. Each component will be described below.
[0013] 1. Matrix polymer The matrix polymer contains a liquid rubber and a solid elastomer, and the mass ratio of the liquid rubber to the solid elastomer is 95:5 to 50:50. This mass ratio is preferably 93:7 to 60:40, and more preferably 90:10 to 70:30. If the ratio of the liquid rubber is too high, the workability is poor, and if the ratio of the liquid rubber is too low, the tracking ability is poor. If the total mass ratio of the liquid rubber and the solid elastomer is 100, the mass ratio of the solid elastomer may be, for example, 5, 10, 15, 20, 25, 30, 35, 40, 45, or 50, or may be within a range between any two of the numerical values exemplified here. The mass ratio of the liquid rubber is a value obtained by subtracting the mass ratio of the solid elastomer from 100.
[0014] The rubber composition contains, for example, 5 to 70 mass %, preferably 6 to 25 mass %, and more preferably 7 to 15 mass % of a matrix polymer, based on 100 mass % of the rubber composition.
[0015] <Liquid rubber> In the present invention, the liquid rubber may be any rubber that is fluid at room temperature, such as liquid polyisoprene, liquid polybutadiene, liquid polychloroprene, liquid polybutene, liquid butyl rubber, etc., but is not necessarily limited to one type, and two or more types may be mixed.
[0016] <Solid elastomer> In the present invention, the solid elastomer may be any elastomer that is solid at room temperature, and examples thereof include natural rubber, isoprene rubber, butadiene rubber, 1,2-polybutadiene rubber, styrene-butadiene rubber, chloroprene rubber, nitrile rubber, butyl rubber, chlorinated butyl rubber, chlorinated polyethylene rubber, ethylene-propylene rubber, ethylene-propylene-diene rubber (EPDM), ethylene-vinyl acetate rubber, chloroprene rubber, chlorosulfonated polyethylene, acrylic rubber, epichlorohydrin rubber, acrylonitrile-butadiene rubber (NBR), crosslinkable rubber such as reclaimed rubber, silicone rubber, fluororubber, urethane rubber, styrene-based thermoplastic elastomer, and the like, but is not necessarily limited to one type, and two or more types may be mixed.
[0017] The styrene-based thermoplastic elastomer is a thermoplastic elastomer having a monomer unit derived from a vinyl aromatic hydrocarbon. The thermoplastic elastomer is an elastomer that has the property of softening and exhibiting fluidity when heated, and can be distinguished from rubber that does not have such a property. The styrene-based thermoplastic elastomer is preferably a block copolymer consisting of a polymer block mainly composed of a vinyl aromatic hydrocarbon and a polymer block mainly composed of a conjugated diene. Examples of the vinyl aromatic hydrocarbon include styrene, p-methylstyrene, α-methylstyrene, vinylxylene, monochlorostyrene, dichlorostyrene, monobromostyrene, etc., which may be used alone or in combination of two or more. Examples of the conjugated diene include 1,3-butadiene, isoprene, 2,3-dimethyl-1,3-butadiene, 1,3-pentadiene, etc., which may be used alone or in combination of two or more.
[0018] Specific examples of styrene-based thermoplastic elastomers include styrene-butadiene-styrene (SBS) copolymer, styrene-isoprene-styrene (SIS) copolymer, styrene-ethylene-butylene-styrene (SEBS) copolymer, styrene-isoprene-hydrogenated styrene-isoprene-styrene (SEPS) copolymer, styrene-ethylene propylene (SEP) copolymer, styrene-ethylene propylene-styrene (SEPS) copolymer, and styrene-ethylene-ethylene propylene-styrene (SEEPS) copolymer.
[0019] The matrix polymer may be composed of only liquid rubber and solid elastomer, or may contain other polymers. Examples of other polymers include resins that are neither liquid rubber nor solid elastomers (polyolefin, polystyrene, etc.). The matrix polymer contains 50% by mass or more of liquid rubber and solid elastomer in total, preferably 80% by mass or more, more preferably 5% by mass, and even more preferably (substantially) 100% by mass of the matrix polymer.
[0020] 2.Metal hydroxide Examples of metal hydroxides include aluminum hydroxide, calcium hydroxide, magnesium hydroxide, etc., but they are not necessarily limited to one type, and two or more types may be mixed.
[0021] The content of the metal hydroxide is 50 to 2000 parts by mass, preferably 250 to 1600 parts by mass, and more preferably 480 to 1200 parts by mass, relative to 100 parts by mass of the matrix polymer. When the content of the metal hydroxide is 50 parts by mass or more, the fire extinguishing property is good. When the content of the metal hydroxide is 2000 parts by mass or less, the flexibility is good, and the followability and adhesion are good. The content of the metal hydroxide is, for example, 50, 100, 150, 200, 250, 300, 350, 400, 450, 480, 500, 550, 600, 650, 700, 750, 800, 850, 900, 950, 1000, 1100, 1200, 1300, 1400, 1500, 1600, 1700, 1800, 1900, or 2000 parts by mass per 100 parts by mass of the matrix polymer, and may be within a range between any two of the numerical values exemplified here.
[0022] 3.Other Ingredients In this embodiment, inorganic compounds other than metal hydroxides used in ordinary rubber compounds, fibrous organic compounds, plasticizers (softeners), antioxidants, processing aids, lubricants, flame retardants, tackifiers, etc. may be used in combination, as long as the effect is not impaired.
[0023] <Inorganic compounds other than metal hydroxides> Examples of inorganic compounds other than metal hydroxides include metal oxides such as alumina, aluminosilicate, zinc oxide, titanium oxide, calcium oxide, magnesium oxide, iron oxide, tin oxide, antimony oxide, and ferrites; smectite clays such as sepiolite, bentonite, montmorillonite, and hectorite, fibrous clays such as palygorskite, clay minerals such as sericite, illite, glauconite, chlorite, talc, zeolite, beidellite, nontronite, saponite, hectorite, sauconite, stevensite, cristoparite, smectite, kaolin, and hydrotalcite; metal carbonates such as basic magnesium carbonate, calcium carbonate, magnesium carbonate, zinc carbonate, strontium carbonate, and barium carbonate; glass fibers (E glass fibers, C glass fibers, S glass fibers, Examples of inorganic fibrous compounds include fibrous inorganic compounds such as zirconia fiber, zirconia fiber, carbon fiber, bulk alkaline earth silicate fiber, gypsum fiber, carbon fiber, metal fiber, slag fiber, and basalt fiber; calcium salts such as calcium sulfate and calcium silicate, glass beads, silica-based baluns, aluminum nitride, boron nitride, silicon nitride, carbon black, graphite, carbon baluns, charcoal powder, various metal powders, potassium titanate, magnesium sulfate, lead zirconate titanate, aluminum borate, molybdenum sulfide, silicon carbide, zinc borate, various magnetic powders, fly ash, inorganic hollow fillers, perlite, obsidian, perlite, rosin, diatomaceous earth, dehydrated sludge, boron, sodium tetraborate hydrate (borax), silica, vermiculite, thermally expandable graphite, and inorganic phosphate compounds. These inorganic compounds may be used alone or in combination of two or more.
[0024] The content of the inorganic compound other than the metal hydroxide is, for example, 0.1 to 100 parts by mass relative to 100 parts by mass of the matrix polymer. The content of the inorganic compound other than the metal hydroxide is, for example, 0.1, 1, 5, 10, 20, 30, 40, 50, 60, 70, 80, 90, or 100 parts by mass relative to 100 parts by mass of the matrix polymer, and may be within a range between any two of the numerical values exemplified here.
[0025] <Thermal expandable graphite> The rubber composition of the present invention may contain thermally expandable graphite. When the rubber composition contains thermally expandable graphite, the thermally expandable graphite expands when heated to form large-capacity voids and functions as a flame retardant, thereby suppressing the spread of fire.
[0026] Thermally expandable graphite is graphite that has the property of thermally expanding by more than 100 times when exposed to a temperature above its expansion onset temperature (approximately 200°C) under normal pressure.
[0027] Such graphite is not particularly limited, but examples thereof include crystalline compounds obtained by surface-treating graphite powder such as natural graphite or pyrolytic graphite with an inorganic acid such as sulfuric acid or nitric acid and a strong oxidizing agent such as concentrated nitric acid or permanganate, and which maintain a graphite layer structure. Note that the graphite powder such as natural graphite or pyrolytic graphite may be deoxidized or further neutralized.
[0028] The content of the thermally expandable graphite is preferably 1 to 300 parts by mass, more preferably 20 to 200 parts by mass, and even more preferably 30 to 150 parts by mass, relative to the mass parts of the matrix polymer. When the content of the thermally expandable graphite is within the above range, large-capacity voids are easily formed in the rubber composition, improving flame retardancy.
[0029] <Inorganic phosphoric acid compounds> The inorganic phosphate compound means a compound including at least one of a phosphoric acid compound, a phosphorous acid compound, a hypophosphorous acid compound, a metaphosphate compound, a pyrophosphate compound, and a polyphosphate compound.
[0030] The phosphate compound is not particularly limited, but examples thereof include aluminum monophosphate, sodium monophosphate, potassium monophosphate, calcium monophosphate, zinc monophosphate, aluminum diphosphate, sodium diphosphate, potassium diphosphate, calcium diphosphate, zinc diphosphate, aluminum triphosphate, sodium triphosphate, potassium triphosphate, calcium triphosphate, zinc triphosphate, magnesium triphosphate, ammonium monophosphate, ammonium diphosphate, tricalcium phosphate, aluminum phosphate, and the like.
[0031] Examples of the phosphite compounds include aluminum phosphite, aluminum hydrogen phosphite, sodium phosphite, potassium phosphite, calcium phosphite, and zinc phosphite.
[0032] Examples of hypophosphite compounds include aluminum hypophosphite, sodium hypophosphite, potassium hypophosphite, calcium hypophosphite, and zinc hypophosphite.
[0033] Examples of metaphosphate compounds include aluminum metaphosphate, sodium metaphosphate, potassium metaphosphate, calcium metaphosphate, zinc metaphosphate, and sodium hexametaphosphate.
[0034] Examples of pyrophosphate compounds include sodium pyrophosphate.
[0035] Examples of polyphosphate compounds include ammonium polyphosphate, sodium polyphosphate, and melamine-modified ammonium polyphosphate.
[0036] Among the inorganic phosphate compounds, ammonium hydrogen phosphite is preferred. The content of the inorganic phosphate compound is preferably 3 to 200 parts by mass, more preferably 5 to 150 parts by mass, and even more preferably 10 to 100 parts by mass, relative to the mass parts of the matrix polymer. When the content of the inorganic phosphate compound is within the above range, the rubber composition exposed to high temperatures and carbonized does not lose its shape, and shape stability is improved.
[0037] <Fibrous organic compounds> The shape of the fibrous organic compound may be fibrous, and examples of the cross-sectional shape of the fiber include a circle, an ellipse, and a polygon. When the average fiber length of the fibrous organic compound is L and the average diameter is D, L / D is, for example, more than 10, preferably 50 or more, and more preferably 100 or more. The upper limit is not particularly specified, but is, for example, 10,000. The average diameter of the fibrous organic compound is, for example, 1 to 100 μm, preferably 2 to 50 μm, and more preferably 5 to 20 μm. The average fiber length of the fibrous organic compound is, for example, preferably 0.5 to 10 mm. This value may be, for example, 0.5, 1.0, 1.5, 2.0, 2.5, 3.0, 3.5, 4.0, 4.5, 5.0, 5.5, 6.0, 6.5, 7.0, 7.5, 8.0, 8.5, 9.0, 9.5, 10.0 mm, or may be within a range between any two of the values exemplified herein.
[0038] Examples of fibrous organic compounds include meta-aramid fibers, para-aramid fibers, amide fibers, cellulose fibers (e.g., pulp fibers), polyparaphenylene benzobisoxazole fibers, polyarylate fibers, polyester fibers, acrylic fibers, acrylonitrile fibers, rayon, silk, cotton, hemp, and wool.
[0039] The average fiber length and average diameter of the fibrous organic compound are determined by measuring the fiber length and diameter of a sufficiently large number of fibrous organic compounds, i.e., 20 or more fibers, and averaging the measured values.
[0040] The fiber length and diameter of the fibrous organic compound can be measured, for example, by using a field emission scanning electron microscope (FE-SEM).
[0041] The content of the fibrous organic compound is 1 to 30 parts by mass, preferably 3 to 24 parts by mass, and more preferably 6 to 17 parts by mass, relative to 100 parts by mass of the matrix polymer. The content of the fibrous organic compound is, for example, 1, 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, 13, 14, 15, 16, 17, 18, 19, 20, 21, 22, 23, 24, 25, 26, 27, 28, 29, or 30 parts by mass, relative to 100 parts by mass of the matrix polymer, and may be within a range between any two of the numerical values exemplified here. When the content of the fibrous compound is within this range, the balance between the cohesiveness and adhesiveness of the rubber composition is improved.
[0042] The rubber composition of the present embodiment can be prepared by kneading the above-mentioned components using a known kneading device such as a Banbury mixer, a kneader mixer, or a two-roll mill, and then molding the mixture using a conventional molding method such as press molding, roll molding, extrusion molding, or calendar molding.
[0043] <Other embodiments> Moreover, a battery according to another embodiment of the present invention includes a member made of the above-mentioned rubber composition. The battery usually has at least one battery cell 3, and the above-mentioned putty-like rubber composition (putty-like composition) is attached to the battery as a member 1 such as a protective material or a fireproof material (FIG. 1). The rubber composition is usually attached to the surface of the battery cell. The battery may have one battery cell or may have two or more battery cells.
[0044] In addition, examples of battery cells include secondary batteries such as lithium ion batteries, lithium ion polymer batteries, nickel-metal hydride batteries, lithium-sulfur batteries, nickel-cadmium batteries, nickel-iron batteries, nickel-zinc batteries, sodium-sulfur batteries, lead-acid batteries, and air batteries, but are not limited to these.
[0045] Batteries are used in, but are not limited to, small electronic devices such as mobile phones and smart phones, laptops, automobiles, power tools, and the like.
[0046] <Laminate> As described above, the rubber composition of the present invention may contain thermally expandable graphite, and in one embodiment of the present invention, the rubber composition may be provided as a laminate in which layers of a fire-resistant sheet or the like containing thermally expandable graphite are laminated.
[0047] The laminate includes, for example, a first layer and a second layer provided on the first layer directly or via another layer. The first layer is made of the rubber composition.
[0048] The second layer is composed of a thermally expandable composition containing thermally expandable graphite. The thermally expandable composition may further contain a matrix polymer in addition to the thermally expandable graphite, and may further contain an inorganic compound.
[0049] The matrix polymer contained in the thermally expandable composition of the second layer is not particularly limited, but examples thereof include rubber, elastomer, thermoplastic resin, thermosetting resin, etc. The matrix polymer may be the same as or different from the matrix polymer contained in the rubber composition.
[0050] The inorganic compound contained in the thermally expandable composition of the second layer is not particularly limited, but can be selected, for example, from the same options as the inorganic compounds (metal hydroxides or inorganic compounds other than metal hydroxides) that can be contained in the rubber composition of the first layer.
[0051] This may be the same as or different from the inorganic compound contained in the rubber composition of the first layer.
[0052] The thermally expandable graphite contained in the thermally expandable composition of the second layer can be selected from the same options as the thermally expandable graphite that can be contained in the rubber composition of the first layer.
[0053] The content of the thermally expandable graphite in the thermally expandable composition of the second layer is preferably 1 to 300 parts by mass, more preferably 20 to 200 parts by mass, and even more preferably 30 to 150 parts by mass, relative to the parts by mass of the matrix polymer.
[0054] In one example, the first layer may not contain thermally expandable graphite and the second layer may contain thermally expandable graphite, and in another example, both the first layer and the second layer may contain thermally expandable graphite.
[0055] The thickness of the second layer is not particularly limited, but is preferably, for example, 0.1 to 20 mm.
[0056] The thickness of the laminate is not particularly limited, but is preferably, for example, 0.2 to 40 mm.
[0057] The thickness ratio of the first layer to the second layer is not particularly limited, but is preferably, for example, first layer:second layer=1:200 (eg, 0.1 mm:20 mm) to 200:1 (eg, 20 mm:0.1 mm).
[0058] Moreover, the laminate may be used as a component for a battery, and a battery according to one embodiment may include the laminate. EXAMPLES
[0059] The present invention will be described in more detail below with reference to examples and comparative examples, but the present invention is not limited to these examples.
[0060] 1. Preparation of Rubber Composition The components shown in the formulations in Tables 1 to 3 were kneaded for 10 minutes at 80° C. using a 3-liter kneader mixer to obtain rubber compositions for the examples and comparative examples, which were then used as test specimens.
[0061] [Table 1]
[0062] [Table 2]
[0063] [Table 3]
[0064] Details of the components in the table are as follows: (1) Matrix polymer <Liquid rubber> Liquid polyisoprene: "LIR-30" manufactured by Kuraray Co., Ltd., molecular weight 28000, Tg: -63℃, viscosity 70 Pa·s (38℃) Liquid polybutadiene: Kuraray Co., Ltd. "LBR-302", molecular weight 5500, Tg: -85℃, viscosity 0.6 Pa s (38℃) Liquid polybutene: JX Nippon Oil & Energy Corporation, "HV-100", molecular weight 980, kinematic viscosity 9,500mm 2 / s(40℃)
[0065] <Solid elastomer> Butyl rubber: JSR Corporation "Butyl 268", rubber-like, softness (21°C) 25 [1 / 10 mm] EPDM: JSR Corporation "EP51", rubber-like, softness (21℃) 17 [1 / 10mm] NBR: "Nipol DN401" manufactured by Zeon Corporation, rubber-like, softness (21℃) 13 [1 / 10mm]
[0066] (2) Metal hydroxide Aluminum hydroxide (Al hydroxide): "C-301N" manufactured by Sumitomo Chemical Co., Ltd. Calcium hydroxide (Ca hydroxide): "Slaked lime" manufactured by Maruai Lime Industry Co., Ltd. Magnesium hydroxide (Mg hydroxide): "KISMA5A" by Kyowa Chemical Substances Co., Ltd.
[0067] (3) Other ingredients <Other resins> EVA: Mitsui DuPont Polychemicals "Evaflex EV460", resin-like, softness (21°C) 7 [1 / 10mm] <Inorganic compounds other than metal hydroxides> Calcium carbonate (Ca carbonate): "TA-044" manufactured by Chichibu Lime Industry Co., Ltd.
[0068] 2. Evaluation The rubber compositions of each of the Examples and Comparative Examples were subjected to the following measurements and evaluations. The results are shown in Tables 1 to 3. As shown in the tables, all of the Examples were good in terms of followability, adhesion, workability (non-adhesiveness), and digestibility. On the other hand, all of the Comparative Examples were not good in at least one of these evaluation items.
[0069] <Conformity (softness)> The softness of the test piece was measured at 21°C under a load of 150g in accordance with JIS A5752. A specified cone was inserted vertically into the test piece, and the penetration depth was measured to the nearest 0.1mm. Based on the penetration depth, the workability was evaluated according to the following criteria. ◎: 60 [1 / 10 mm] or more ○: 50 [1 / 10 mm] or more and less than 60 [1 / 10 mm] △: 40[1 / 10mm] or more and less than 50[1 / 10mm] ×: Less than 40 [1 / 10 mm]
[0070] <Tackiness> As shown in Figure 2, a 3g spherical test piece 5 was sandwiched between two aluminum plates 7 specified by JIS H4000 (A1050) and compressed to a thickness of 5mm, and after 1 minute, it was peeled vertically at a peeling speed of 300mm / min, and the adhesion was measured based on the peak strength at the time of peeling. The adhesion was then evaluated according to the following criteria. ◎:3[N] or more ○: 2[N] or more and less than 3[N] △: 1[N] or more and less than 2[N] ×: Less than 1[N]
[0071] <Workability (non-adhesiveness)> After measuring the mass of the latex glove, the latex glove was put on and a 100g spherical test piece (putty) was gripped 10 times, after which the weight of the deposit on the glove was measured and the weight of the deposit was calculated based on the following formula. Based on the weight of the deposit, the non-adhesiveness was evaluated according to the following criteria. Weight of the deposit [g] = (weight of the glove after squeezing the putty 10 times) - (original weight of the glove) [Evaluation Criteria] ◎: The weight of the attached matter is less than 0.5 g. ◯: The weight of the deposit is 0.5 g or more and less than 1.0 g. △: The weight of the attached matter is 1.0 [g] or more and less than 1.5 [g]. ×: The weight of the attached matter is 1.5 g or more.
[0072] <Fire extinguishing properties> A test specimen was created by placing the test pieces around a laminated lithium-ion battery used in smartphones so that it completely covered the battery.The test specimen was then placed on a hot plate set at 300°C and the time from the release of fire to the extinguishing of the fire was evaluated.A shorter fire extinguishing time indicates better fire extinguishing performance. ◎: Extinguishing time is less than 3 seconds ○: Extinguishing time is between 3 and 5 seconds △: Extinguishing time is between 5 and 10 seconds ×: Fire extinguishing time is 10 seconds or more
Claims
1. 50 to 2000 parts by mass of a metal hydroxide per 100 parts by mass of a matrix polymer; the matrix polymer comprises a liquid rubber and a solid elastomer, and the mass ratio of the liquid rubber to the solid elastomer is 95:5 to 50:50; the content of the inorganic compound other than the metal hydroxide is 50 parts by mass or less relative to 100 parts by mass of the matrix polymer; The solid elastomer is rubbery; A rubber composition having a softness at a temperature of 21°C, measured in accordance with JIS A5752, of 40 [1 / 10 mm] or more and 95 [1 / 10 mm] or less.
2. The rubber composition of claim 1 , wherein the metal hydroxide comprises aluminum hydroxide.
3. The composition contains 50 to 2000 parts by mass of a metal hydroxide relative to 100 parts by mass of a matrix polymer, the matrix polymer comprises a liquid rubber and a solid elastomer, and the mass ratio of the liquid rubber to the solid elastomer is 95:5 to 50:50; the content of the inorganic compound other than the metal hydroxide is 50 parts by mass or less relative to 100 parts by mass of the matrix polymer; The solid elastomer is rubbery; The rubber composition is in a putty form.
4. The rubber composition according to any one of claims 1 to 3, which is used in a battery.
5. A battery comprising a member made of the rubber composition according to any one of claims 1 to 3.
Citation Information
Patent Citations
Fireproof putty composition
JP1994306364A
Thermally expandable putty composition
JP2007254563A
Battery pack and equipment equipped with battery
JP2009021223A
Non-hardenable refractory putty composition
JP2014095068A
Fire-resistant resin composition, fire-resistant sheet, and battery
JP2019143139A